Avaliação cardiorrespiratória em ratos submetidos à convulsão por eletrochoque - Furtado, Danielly Peres (2010)
The aim of this study was to evaluate the cardiopulmonary changes after induction of electroshock seizures (ES) in rats. We used 113 Wistar rats weighing 250-350g. Under anesthesia, we performed implantation of ears electrodes for the induction of ES and catheterization of the femoral vessels to allow cardiovascular recordings. Measures of mean arterial pressure (MAP) and heart rate (HR) were made before and after 0.3, 2, 5, 10, 15, 20, 25 and 30 minutes post-ES in awaked animals. Respiratory rate (RR), tidal volume (VT) and pulmonary ventilation (Vmin) were evaluated before and after the induction of ES, using the technique of whole-body plethysmographic chamber. The autonomic components were assessed by blockade of β1-adrenoceptors with atenolol and muscarinic colinoceptors with methyl-atropine. The cardiovascular reflexes were assessed by injection of potassium cyanide (KCN) (chemoreflex); fenilbiguanide (FBG) (Bezold-Jarisch reflex) and sodium nitroprusside and phenylephrine (baroreflex). The effects of sino-aortic denervation (SAD) and peripheral adrenergic blockade with atenolol and prazosin (α1-adrenergic antagonist) on responses to induction of ES were also evaluated. The results showed a significant increase in MAP at 0.3 and 2 minutes postES (134 ± 6 and 123 ± 5 mmHg, respectively) compared to control values pre-ES (100 ± 2 mmHg). There were no significant differences among other moments. For baseline HR, compared to control values pre-ES (392 ± 8 bpm) a significant reduction was observed (p<0.01) at 0.3 minutes after electroshock. A significant reversal of HR was observed after 15 (446 ± 13 bpm), 20 (454 ± 10 bpm), 25 (470 ± 7 bpm) and 30 (477 ± 7 bpm) minutes post-ES compared to control values. Regarding the autonomic components (sympathetic and parasympathetic) we observed that the ES caused a significant increase in parasympathetic activity during the post-ictal period (1 minute), followed by a progressive attenuation of this component at 2, 5, 10, 20 and 30 minutes post -ES. In relation to the sympathetic component, we initially observed a progressive increase since from one minute after the ES, which was statistically significant at 5 (17 ± 2* bpm), 10 (26 ± 5** bpm) 20 (34 ± 6** bpm) and 30 (45 ± 6** bpm) minutes after the electroshock when compared to the first minute (-2 ± 2 bpm). After double blockade with atenolol and methyl-atropine, we observed significant increase (p<0.01) in the MAP values after 1 (156 ± 2 mmHg) and 2 (135 ± 6 mmHg) minutes after ES when compared to control values (97 ± 4 mmHg). There was no significant difference among the MAP values at 5, 10, 20 and 30 minutes after the ES and control values. Regarding the respiratory parameters, it was observed apnea during ictal and post-ictal periods in 78% of animals. In addition, there was significant increase of the VT values (p<0.01) at 0.3 (11.4 ± 0.6) and 2 (12.2 ± 0.8) minutes after ES compared to the control (7.1 ± 0.3). In relation to the RR, there was a significant reduction (p<0.01) at 0.3 minutes (67 ± 3 cam) compared to control (97 ± 6 cam). In the same way, in relation to Vmin we observed a significant increase (p<0.01) only at 2 minutes after the induction ES (1249 ± 120) compared to the control (677 ± 36). To the chemoreflex, we observed that KCN produced pressor responses (48 ± 3 mmHg), which was significantly reduced after the induction of ES at 1 (33 ± 4 mmHg) and 5 (34 ± 4 mmHg) minutes compared to control (48 ± 3 mmHg). There was no statistical difference among the other moments after the ES. With regard to HR chemoreflex, there was significant reduction in the first minute post-ES (-106 ± 9 bpm) when compared to control (-194 ± 11 bpm), however, this response was significantly higher compared to control group at 5 (- 263 ± 13 bpm), 10 (-262 ± 16 bpm), 20 (-274 ± 16 bpm) 30 (-253 ± 16 bpm) minutes after the induction of ES. With regard to the Bezold-Jarisch reflex, it was observed initially that the injection of FBG produced hypotensive (-48 ± 2 mmHg) and 22 bradycardic (-248 ± 11 bpm) responses. These hypotensive responses were not statistically different from the control after the induction of ES. In relation to bradycardic response, we observed a significant attenuation in the first minutes after the ES, i.e., at 0.3 (-157 ± 16 bpm) and 2 (-110 ± 16 bpm) minutes when compared to control values (- 248 ± 11 bpm). There were no significant differences in the remaining moments after the ES. Regarding the baroreflex, we observed that only the gain measured in response to bradycardia phenylephrine-induced for 2 minutes after induction of ES was significantly attenuated. After SAD, there was significant attenuation of the bradycardic response induced by ES, which was also observed in the group submitted to blockade with atenolol+prazosin. The results of this study suggest that the tonic-clonic seizures induced by electroshock produced major changes in the: a) cardiovascular system, characterized by hypertensive and bradycardic responses, b) respiratory system, characterized by apnea, hyperpnea and bradypnea observed immediately after induction of ES, c) a significant impairment of the cardiovascular reflexes responses (chemoreflex, BezoldJarisch reflex and baroreflex), d) autonomic dysfunctions observed in the ictal period, in which we observed a significant increase of the cardio-vagal and sympathetic vascular autonomic activities. In the post-ictal period, only an increased cardiac sympathetic activity was observed. Thus, at least in part, this cardio-vagal response is mediated by arterial baroreceptors.